PENERAPAN TEKNOLOGI SMART PACKAGING (PEGI MEJING) UNTUK MENINGKATAN KUALITAS PRODUK KOPI PADA KELOMPOK TANI TEBAT EMPAI SUBUR - Lesi Anggraini; Febriansyah; Abdi Narullah (Fakultas Pertanian, 2025)
The Smart Packaging Technology Implementation Program to Improve Coffee Product Quality at the Tebat Empai Subur Farmers Group aims to increase the added value and competitiveness of local coffee products through modern packaging technology innovations. Prior to this initiative, the packaging process was still carried out manually, resulting in decreased product quality, unattractive packaging, and low sales value. The program aims to improve the quality and sales value of local coffee products through the implementation of modern packaging technology innovations. Activities include outreach, training, mentoring, and direct implementation in the field. Through this PKM activity, the community was introduced to and trained in the use of Smart Packaging machines, digital scales, and modern packaging designs that meet market standards. The implementation results show significant improvements in product quality, time efficiency, and human resource skills. Coffee products are now packaged more hygienically, last longer, and have an attractive appearance for consumers. Economic value has also increased as products are marketed through souvenir shops, local markets, and social media platforms such as Facebook, Instagram, and TikTok